An insider view of the hybrid organisation: How managers respond to challenges of efficiency, legitimacy and meaning. (16th February 2015) - Johansen, Svein T.; Olsen, Trude H.; Solstad, Elsa; Torsteinsen, Harald
Abstract: In this paper we look at how managers perceive and manage meetings between different institutional logics in three types of hybrid organisations; a savings bank, a municipality and a hospital. The paper contributes to our understanding of organisational hybridity in two ways: First, drawing on Scott's three institutional pillars, the paper shows how meetings between different institutional logics involve not just the cultural–cognitive pillar, usually highlighted in work on hybrid organisations, but all of them, including the regulative and the normative pillars. Second, the paper suggests a hierarchical relationship between meetings and responses, ranging from less elaborate responses that primarily involve the regulative pillar to more complex and all-encompassing responses that include not only the regulative and the normative but also the cultural–cognitive pillar, triggering questions and issues about identity and purpose.